Towards sustainable urban futures: A process for placemaking in South African townships - Wessel Strydom; Karen Puren; Ernst Drewes (Town and Regional Planning)
While placemaking has gained global traction, South Africa lacks a locally adapted process to guide planners, policymakers, and communities in harnessing its potential – particularly in historically marginalised township settings. Amidst rapid urbanisation and growing socio-spatial disparities, there is a pressing need for innovative and context-sensitive development approaches. This article explores the potential of placemaking as a strategy for sustainable urban development and community empowerment within South African townships. Adopting a case study approach, the study focuses on Marabastad in Kroonstad (Free State province), a township emblematic of the broader structural and spatial challenges faced by the country. The theoretical foundation draws from placemaking literature in both the Global North and South, mapping a shift from static, product-oriented understandings to more dynamic, iterative, and participatory processes. This shift informs the exploration of placemaking’s four core dimensions, namely physical, social, economic, and psychological, prevalent in South African contexts. Empirical data were collected through qualitative methods, including interviews, observations, and participatory approaches, and analysed thematically. The findings reveal opportunities for community engagement, economic activation, cultural recognition, and spatial transformation. Drawing from these insights, the article proposes a five-phase placemaking process specifically adapted to South African townships: community orientation and grounding; contextual analysis and exploration; identification of placemaking interventions; strategic planning and design, as well as implementation, maintenance and evolution. This process emphasises active community participation, local knowledge, and skills development, offering a scalable and adaptable pathway for co-producing vibrant, inclusive, and resilient urban spaces.